2012
DOI: 10.1007/978-3-642-27278-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Data Analysis of Cold Rice Blast Based on Near Infrared Spectroscopy

Abstract: In order to overcome the low diagnostic accuracy of traditional blast visual defects, set cold rice blast for example, four data groups has been acquainted through near infrared spectroscopy, the first group is healthy and diseased planting stock; the second group is three diseased levels of leaf blast; the third group is five diseased levels of grain blast; the forth group is four diseased levels of panicle blast, according to the analysis, we can know that different circumstances of plants had their own near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Some previous work has focused on a combination of pests and diseases, for example in [10] where a multi-spectral imaging methodology for the diagnosis of plant diseases and insect pests was employed. The use of near-infrared spectroscopy to analyze cold rice blast is also discussed in [11]. Similarly, hyper-spectral data were used for the pre-symptomatic detection of infections in sugar beet in [12].…”
Section: Related Workmentioning
confidence: 99%
“…Some previous work has focused on a combination of pests and diseases, for example in [10] where a multi-spectral imaging methodology for the diagnosis of plant diseases and insect pests was employed. The use of near-infrared spectroscopy to analyze cold rice blast is also discussed in [11]. Similarly, hyper-spectral data were used for the pre-symptomatic detection of infections in sugar beet in [12].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, the general data systems of spectroscopy consist of a general computer connected to a printer that can produce high-quality spectra, as well as a software programme that includes spectrum acquisition offer, spectral transform, spectral processing, spectral analysis, and all other functions. Besides, users can also create their own operational procedures of spectral data for their needs (Tan et al, 2012).…”
Section: Spectroscopy-based Techniquesmentioning
confidence: 99%
“…The strength of FTIR is its speed advantage which makes it possible to obtain spectra on a millisecond timescale. Tan et al (2012) employed the NIR spectroscopy for detection of cold rice blast in cold land, which consisted of the healthy rice plant, three diseased levels of leaves blast, five diseased levels of grain blast, and four diseased levels of the infected stem. The study adopted the multi-spectral vision technology to investigate the identified classification test on the rice varieties, which had been resistance to disease.…”
Section: Spectroscopy-based Techniquesmentioning
confidence: 99%